2001
DOI: 10.2134/jeq2001.302460x
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Nickel and Other Metals in Contaminated Sediments by Hydroxyapatite Addition

Abstract: ABSTRACTnah River Site (SRS) near Aiken, SC, is a prime example, having been contaminated with a variety of metals. proximately 5.3 ha, and the potential to drastically disturb the Upper Three Runs/Tims Branch stream system and possibly enhance contaminant transport due to ero-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 34 publications
2
110
1
1
Order By: Relevance
“…The formation in contaminated soils of insoluble lead compounds following AP addition has been suggested (Greman et al, 2001;Seaman et al, 2001) and demonstrated (Laperche et al, 1997;Ryan et al, 2001). Fewer works have been undertaken on other potentially hazardous elements, but the precipitation of metal phosphate compounds (e.g., Ni, Zn, Cd) was suggested from laboratory and field studies (Valsami-Jones et al, 1998;Greman et al, 2001;Seaman et al, 2001), although these compounds are more soluble than Pb-phosphates. When Zn 2+ is added to AP suspension, laboratory experiments showed that this element reacts with AP or the solute species resulting from its dissolution (Xu and Schwartz, 1994;Peaudecerf, 2002) (Fuierer et al, 1994;Xu and Schwartz, 1994) and, in addition, on the proton activity since the dissolution rate of AP is pH-dependent (section 2.1.3, and Valsami-Jones et al, 1998).…”
Section: Effect Of Amendments On Zn Speciationmentioning
confidence: 95%
See 2 more Smart Citations
“…The formation in contaminated soils of insoluble lead compounds following AP addition has been suggested (Greman et al, 2001;Seaman et al, 2001) and demonstrated (Laperche et al, 1997;Ryan et al, 2001). Fewer works have been undertaken on other potentially hazardous elements, but the precipitation of metal phosphate compounds (e.g., Ni, Zn, Cd) was suggested from laboratory and field studies (Valsami-Jones et al, 1998;Greman et al, 2001;Seaman et al, 2001), although these compounds are more soluble than Pb-phosphates. When Zn 2+ is added to AP suspension, laboratory experiments showed that this element reacts with AP or the solute species resulting from its dissolution (Xu and Schwartz, 1994;Peaudecerf, 2002) (Fuierer et al, 1994;Xu and Schwartz, 1994) and, in addition, on the proton activity since the dissolution rate of AP is pH-dependent (section 2.1.3, and Valsami-Jones et al, 1998).…”
Section: Effect Of Amendments On Zn Speciationmentioning
confidence: 95%
“…The precipitation of sparingly soluble Pb-phosphates, namely Pb hydroxy-and chloro-pyromorphite (K sp =10 -63.1 and 10 -84.4 , respectively; Nriagu, 1984), after the addition of AP, has been extensively reported from laboratory experiments under medium to moderately acidic conditions (Ma et al, 1993;Lower et al, 1998;Valsami-Jones et al, 1998;Zhang and Ryan, 1999). The formation in contaminated soils of insoluble lead compounds following AP addition has been suggested (Greman et al, 2001;Seaman et al, 2001) and demonstrated (Laperche et al, 1997;Ryan et al, 2001). Fewer works have been undertaken on other potentially hazardous elements, but the precipitation of metal phosphate compounds (e.g., Ni, Zn, Cd) was suggested from laboratory and field studies (Valsami-Jones et al, 1998;Greman et al, 2001;Seaman et al, 2001), although these compounds are more soluble than Pb-phosphates.…”
Section: Effect Of Amendments On Zn Speciationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Barcelona and Holm (1991), Pantsar-Kallio et al (2001) and Seaman et al (2001) reported that oxidation and reduction reactions are important in the fate, transport and toxicity of Cr in the soil. These reactions are governed by many factors including organic matter, pH, aeration, soil moisture content, wetting and drying, microbial activity, clay mineral content and availability of electron donors and acceptors.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the coupled effects of the pH and EC on the Cr concentration in BL for two different values of DOC (14 and 34 mg.l -1 ). (2001) and Seaman et al (2001) reported that oxidation and reduction reactions are important in the fate, transport, and toxicity of Cr in the soil. These reactions are governed by many factors including organic matter, pH, aeration, soil moisture content, wetting and drying, microbial activity, the content in clay minerals and availability of electron donors and acceptors.…”
Section: Neural Network Modeling Resultsmentioning
confidence: 99%